A microstructural based creep model applied to alloy 718. (June 2018) - Drexler, Andreas; Fischersworring-Bunk, Andreas; Oberwinkler, Bernd; Ecker, Werner; Gänser, Hans-Peter
Abstract: In this work a creep model based on the microstructural evolution of precipitation strengthening metals is presented. The model describes the influence of precipitates on the threshold stress as well as the power-law and the exponential creep rates depending on the aging condition. To show the predictive capabilities of this model, it was applied to the nickel based superalloy Alloy 718. This alloy is precipitation strengthened by the γ′ and γ'' phases. Thermo-kinetic simulations based on a calibrated MatCalc routine were performed to determine the evolution of the volume fraction and mean radius of the precipitates. In addition, sequential creep and tensile tests were performed to characterize the mechanical material behavior. The simulated microstructural evolution and the corresponding measured mechanical properties were used to parametrize the creep model. Finally, the fully parametrized model was applied to simulate deformation mechanism diagrams for different aging conditions. From these diagrams the purely elastic, the power-law and the exponential deformation regimes can be estimated depending on the precipitate volume fraction and mean precipitate radius. Highlights: A microstructurally based creep model accounting for the precipitation strengthening is proposed. The creep model is applied to the widely used nickel-based superalloy Alloy 718. Deformation mechanism diagrams for the half-aged and aged material were presented.